Vivência de mulheres no puerpério : significado atribuído à revisão pósparto - Santos, Flavia Andreia Pereira Soares dos (2011)
The consultation for women during the postpartum period should occur between the seventh and tenth days, and 42 days after childbirth, to decrease the incidence of maternal and neonatal morbidity and mortality. However, the effectiveness of such assistance in primary health care has not been achieved, especially in the forty-second day of puerperium. Facing this reality, the research aimed to understand the views of women about postpartum consultation. This is an exploratory and descriptive research with qualitative approach, developed in the municipality of Lajes/RN, Brazil, with women inscribed on the four teams that make up the Family Health Strategy. Data were collected through semistructured interviews with 15 women who met the following criteria: be enrolled in ESF; have health mental preserved, have been entered in the Humanization Program of Prenatal and Birth, and that was, at maximum, 60 days postpartum. The data were organized according to the precepts of content analysis according to Bardin, generating three categories: prevention of puerperal complications, feelings related to life changes after childbirth, and postpartum care. This process of coding and categorizing a central theme emerged: the experience of women in the postpartum period. The data were analyzed according to the principles of symbolic interactionism, according to Blumer. The study revealed that the meanings attributed to the postpartum period for prevention of complications were directly related to home, to the consultation and postpartum care provided by family members and health professionals. The interviewees strictly complied with the rest under the influence of the context in which they were entered. But that has not happened with the postpartum revision because few mothers underwent this procedure. Therefore, the interaction of the interviewed people in their living standard as well as the feelings that permeated the post-partum were crucial to consider whether or not the post-partum visit as significant. According to the results, it was noted that disability guidelines and counter-references has impaired the access of women to postpartum review. Thus, further studies are needed on the subject, as well as a reorientation of health care activities in view of the consolidation of postpartum consultation in primary care